HUBUNGAN PENGETAHUAN DAN JENIS MAKANAN YANG DI KONSUMSI UNTUK MENCEGAH ANEMIA PADA REMAJA DI PEKANBARU - Yusmaharani Yusmaharani; Rini Hariani Ratih; Nurmaliza Nurmaliza (LPPM Universitas Abdurrab, 2023)
Adolescence requires a balanced nutritional intake for growth and development, one of which is iron. Teenage girls really need iron during menstruation. Iron deficiency can increase the risk of anemia, namely a lack of red blood cells or hemoglobin (Hb), this condition makes people with anemia look pale, tired and weak, and can continue into adulthood and affect conditions during pregnancy. This study aims to determine the relationship between knowledge and the type of food consumed to prevent anemia in adolescents in Pekanbaru. This research is quantitative analytic with a cross-sectional research design. This research was conducted at SMAN 8 Pekanbaru, the sample was taken by purposive sampling. The number of samples as many as 65 respondents. The analysis was carried out univariate and bivariate. The results of the study showed that the majority of young women's knowledge was good as many as 40 people (61.5%), the majority consumed foods containing a lot of heme iron as many as 49 people (75.4%). The results of the univariate analysis of the majority of respondents have good knowledge about anemia as many as 40 people (61.5%) and the majority of young women consume foods that contain a lot of iron as many as 49 people (75.4%). The results of bivariate analysis using chi square obtained P value = 0.01 < 0.05, this means that there is a relationship between knowledge about anemia and the type of food consumed by young women. It is recommended for schools to work together with the Health and often conduct counseling and distribution of free Fe tablets and disseminate information about anemia in school maddings so that all young girls always remember the importance of consuming foods containing iron to avoid anemia